Minimising Coal Damage and Loss Due to Cast Blasting - Tapan Goswami (International Society of Explosives Engineers, 2020)
This paper discusses the importance of coal mapping, the rock properties of the roof and floor interface of the coal seam, and the significance of loading and initiating designs in minimising coal damage. Furthermore, the importance of using electronic initiators cannot be emphasised enough. This paper also discusses how a cast blast can be initiated from many locations by mitigating geological abnormalities and thereby avoiding spatial movement of rock shearing in a plane above the coal seam.